PREPARING A STUDENT TEAM BASED ON INNOVATIVE DIRECTIONS IN MINI-FOOTBALL - Davranov E. O., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the innovative methods used in the training of the student team in mini football, their effectiveness and approaches aimed at improving the quality of the athletes' game. Modern training processes, technical and tactical exercises, as well as important aspects of physical and mental preparation are considered for successful participation in competitions among students. The methods used in order to improve the team's level of play and achieve high results in the future through innovative approaches are discussed.